2012
DOI: 10.2109/jcersj2.120.473
|View full text |Cite
|
Sign up to set email alerts
|

Direct observation of the cleavage plane of sapphire by in-situ indentation TEM

Abstract: TEM in-situ indentation experiments were applied to directly observe the atomic structures on the cleavage planes of sapphire, and the structures were determined by HRTEM image simulation. It was found that cracks mainly propagate along the low index planes of sapphire, forming the atomic scale steps on the cleavage planes, and the atomic structures are dependent on the crystal orientation. In addition, the surface structures of the cleavage planes were found to be reconstructed in the vicinity of the respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…A structural rearrangement within the crack tip zone in sapphire manifested in formation of metastable Al-O-Al clusters at its fracture surface has been recently reported [24].…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…A structural rearrangement within the crack tip zone in sapphire manifested in formation of metastable Al-O-Al clusters at its fracture surface has been recently reported [24].…”
Section: Introductionmentioning
confidence: 91%
“…It should be noted that substitution of (24,38) into the effective free energy, (17) yields the LPT free energy:…”
Section: The Overcritical Solutionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thereafter, TEM in situ straining became popular for clarification of the dislocation dynamics in various materials with face-centered cubic (fcc) [ 6 , 9 , 10 , 11 ], body-centered cubic (bcc) [ 12 , 13 , 14 ], and hexagonal close-packed structures [ 15 , 16 ] during plastic deformation at various temperatures. For brittle fracture, Ikuhara et al [ 17 ] developed a TEM indentation holder working at elevated temperatures and reported the crack propagation by intra- and intergranular fracture in polycrystalline alumina at 1073 K. This indentation technique has been applied to several ceramic materials with brittle nature, such as magnesium oxide, silicon nitride, and sapphire (α-Al 2 O 3 ) [ 18 , 19 , 20 , 21 ]. To clearly visualize the dislocations introduced during TEM in situ indentation experiments, Kondo et al [ 22 , 23 ] recently used a double-tilt indentation holder and characterized an individual dislocation in a SrTiO 3 single crystal and well-oriented SrTiO 3 bicrystals with Σ5 and small-angle grain boundaries.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, post-mortem characterization by atomic-resolution TEM is often carried out to obtain detailed information at the atomic level. For alumina, crack propagation (Sasaki et al 2012;Kondo et al 2019) and dislocation formation phenomena (Miao et al 2019) have been investigated by in situ indentation and atomic structure analysis so far.…”
mentioning
confidence: 99%